Using Social Marketing to Reduce Salt Intake in Iran - Layeghiasl, Mehdi; Malekzadeh, Janmohamad; Shams, Mohsen; Maleki, Mostafa (Frontiers in Public Health, 2020)
Objectives: WHO has recommended that the average salt intake must be less than 5 grams per day. However, people consume salt much more in many countries. In this study, we design and implement an intervention based on social marketing model to reduce salt consumption in Yasuj, Iran. Materials and Methods: This field trial study was consisted of formative research (qualitative-quantitative) and an interventional phase. To collect the qualitative data, six focus group discussions by participating of 66 people were established. The qualitative data were analyzed manually using directed content analysis. In quantitative study, 166 people aged 25-50 years completed a KAP questionnaire, and their average salt intake was determined through measuring sodium in their urine sample. By analyzing the data, marketing mix components were determined for designing an intervention. An educational package (including posters for installing in the kitchen, pamphlets, phone counseling, four educational classes, and brief interventions done by physicians and other health personnel) focused on reducing salt intake and using alternatives was developed. For one month, program was implemented for the intervention group. Two months later, KAP survey and measuring the urine sodium were repeated for intervention and control groups. The data was compared for two groups, before and after intervention. Results: The qualitative findings showed that most participants agreed that the salt intake was high in Iran. Most of them recommended home-based and family-driven strategies to reduce salt intake, offered using healthier alternatives for salt, and recognized physicians and health care providers in healthcare facilities as the most important to encourage people to reduce salt intake. The quantitative findings showed the average salt intake was 14±3.52 g/day. Most participants had intermediate scores of knowledge, attitudes, and practice. After the intervention, the mean and standard deviation of knowledge, attitudes, practice, urine sodium, and salt intake become better significantly in the intervention group compared to the control group. Conclusion: The mean salt intake among the study population was approximately three times more than the level recommended by the WHO. The social marketing-based intervention succeeded in reducing the salt intake of the study subjects by approximately 3 grams on average